Analysis of mooring performance and layout parameters of multi-segment mooring system for a 15 MW floating wind turbine - Huang, Jianwu; Xu, Hang; Chen, Li; Lin, Kuigeng; Guo, Mingyuan; Yang, Mindong; Rui, Shengjie (Frontiers in Energy Research, 2024)
Introduction Floating wind power is the important path for the development of offshore wind energy, and the performance of the mooring system of floating wind turbines (FOWTs) significantly affects their economic viability, safety, and sustainability. Methods This paper systematically analyses the positioning performance, mooring line extreme loads, and fatigue response of a FOWT equipped with both single segment and multi-segment mooring systems, based on the IEA 15 MW large turbine and a floating platform. The hydrodynamic performance of the floating platform is calculated, and the platform’s motion-sensitive directions are analysed through Response Amplitude Operators (RAOs). The natural periods of the platform are validated by free decay tests. The six degrees of freedom (DOFs) motion response and the mooring line peak tensions are analysed under normal and extreme conditions. Results The results show that both mooring systems provide good motion performance and stable tilt angles for the platform. Under ALS (single-line failure) condition, the multi-segment mooring system demonstrates a notable capacity to resist impact loads, with comparatively minor fluctuations in mooring line tension. In the multi-segment system, fatigue damage primarily occurs in the upper mooring chain, with damage approximately 4.5 times greater than that of the bottom chain over a 1-year period. The effects of mooring line spread angles and lengths on performance are also analysed. The results indicate that the mooring line spread angle has slight impact on platform motion response and mooring line tension, while mooring line length significantly affects the extreme tension of the lines. Discussion The findings of this study can provide some references in the design of mooring systems for future FOWTs.